2016
DOI: 10.14260/jemds/2016/733
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial of Vacuum-Assisted Closure Versus Standard Therapy of Chronic Non-Healing Wounds

Abstract: BACKGROUNDThe application of controlled levels of negative pressure has been shown to accelerate debridement and promote healing in many different types of wounds. The optimum level of negative pressure appears to be around 125 mmHg below ambient and there is evidence that this is most effective if applied in a cyclical fashion of five minutes on and two minutes off. It is believed that the negative pressure assists with removal of interstitial fluid, decreasing localised oedema and increasing blood flow. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…They concluded that VAC care aided the quick production of granulation tissue, reducing healing time and secondary soft-tissue defect-covering procedures. Similar investigations by Joseph et al [28], Morykwas and Argenta [14], and Morykwas et al [15]. found that VAC was more successful than traditional wound dressings in lowering wound widths over time.…”
Section: Discussionsupporting
confidence: 65%
“…They concluded that VAC care aided the quick production of granulation tissue, reducing healing time and secondary soft-tissue defect-covering procedures. Similar investigations by Joseph et al [28], Morykwas and Argenta [14], and Morykwas et al [15]. found that VAC was more successful than traditional wound dressings in lowering wound widths over time.…”
Section: Discussionsupporting
confidence: 65%
“…In a small-sample clinical trial, Raghupathy et al indicated that Negative Pressure Wound Therapy (NPWT) significantly reduced the complete healing time of chronic wounds. 86 However, NPWT is not without limitations, including:…”
Section: Primary Therapeutic Measures For Diabetic Wound Treatmentmentioning
confidence: 99%
“…In a small-sample clinical trial, Raghupathy et al indicated that Negative Pressure Wound Therapy (NPWT) significantly reduced the complete healing time of chronic wounds. 86 However, NPWT is not without limitations, including: Complications: Potential complications encompass bleeding (including wound oozing and vascular bleeding), local pain, malodor, wound infection, and damage to surrounding tissues. Severe complications may precipitate septic shock, intestinal fistula, and hemodynamic instability.…”
Section: Challenges Of Diabetic Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique was first described by Fleischmann et al in 1993, following the successful use of this technique in 15 patients with open fractures. 5 The study reported that treatment resulted in "efficient cleaning and conditioning of wound with marked proliferation of granulation tissue". Following Fleischmann, VAC has been successfully used as an adjunct therapy in the treatment of acute and chronic soft tissue defects, defects with exposed hardware, enterocutaneous fistulae, sternotomy wounds, burns and after skin graft has been applied.…”
Section: Introductionmentioning
confidence: 99%